Assessment of Groundwater Nitrate Pollution and Determination of Groundwater Protection Zones Using DRASTIC and Composite DRASTIC (CD) Models: The Case of Shiraz Unconfined Aquifer - Mohammad Ali Baghapour; Nasser Talebbeydokhti; Hamidreza Tabatabee; Amir Fadaei Nobandegani (Shiraz University of Medical Sciences, 2014)
Background: Groundwater nitrate pollution is an important environmental problem in water resources management. In this regard, specific measures aiming at prevention of water pollution will be helpful to managers and decision-makers. Identification of aquifers' vulnerable areas and determination of groundwater protection zones using most widely used models, such as DRASTIC and CD, are one of the most useful approaches in water resources' hygiene. Objective: The present study aimed to assess the vulnerability of Shiraz plain's unconfined aquifer using the above-mentioned models. Methods: The main hydro-geologic factors affecting the transmission of pollution, including depth to water table, net recharge, aquifer media, soil media, topography, impact of the vadose zone, aquifer hydraulic conductivity, and land use parameters were rated, weighted, and integrated using GIS 9.3. Finally, the maps of Shiraz plain's unconfined aquifer vulnerability were prepared. Results: The vulnerability maps based on these two indexes showed very similar results, identifying the southeastern part of the aquifer, around Maharlu Lake, as the vulnerable zone. The observed nitrate concentrations from the wells in the underlying aquifer were in accordance with these findings. The results of sensitivity analyses indicated the depth parameter as the most effective parameter in vulnerability assessment of Shiraz plain. Conclusion: As Shiraz plain has been covered with fine-grained sediments, except for some central and south-east regions which have moderate vulnerability and high nitrate concentration, its vulnerability is low. Given the intensive agricultural activities and also the rise in groundwater level in southeastern regions, more attention should be paid to these areas.